Enhancing the dimethyl ether carbonylation performance over mordenite catalysts by simple alkaline treatment. (1st March 2019) - Wang, Xiaosheng; Li, Ranjia; Yu, Changchun; Liu, Yuxiang; Zhang, Liya; Xu, Chunming; Zhou, Hongjun
Graphical abstract: Highlights: Alkaline treated MOR catalysts were prepared with the presence of templates. Mesopores and macropores formed after the alkaline treatment. Strong acid sites were protected by templates in alkaline treatment process. The stability of modified MOR catalysts in the carbonylation reaction was improved. The coke deposition were suppressed over the modified MOR catalysts. Abstract: In this paper, post-synthesis modified MOR catalysts were prepared by alkaline treatment with and without the presence of templates. To investigate the modification effect of alkaline treatment to the structure and acid sites, the obtained catalysts were characterized by XRD, N2 adsorption-desorption, SEM, 29 Si NMR, 27 Al NMR, NH3 -TPD and FTIR. The characterization results showed that the crystallinity of all samples decreased while specific surface area and pore volume increased to some extent. Certain amount of Si species and fewer amount of Al species were removed out during the alkaline treatment process, thus leading to the formation of mesopores and macropores. The protective effect of templates to the strong acid sites in the 8 MR and micropores were remarkable. Without the presence of templates, part of the micropores would be destroyed and the strong acid sites would largely be removed. Over the samples that had been alkaline modified with templates inside the micropores, the carbonylation performance still remained the same and the single-pass lifespan gradually extended due to the enhanced mass transfer efficiency and decreased acid sites in the diffusion paths. The side reactions were largely inhibited and the amount of coke deposition also decreased, which demonstrated that retaining the templates during the alkaline treatment was an effective way to enhance the DME carbonylation performance and suppress the coke deposition during the carbonylation process at the same time.